About the silicon sensitivity of the deep level with alternating pressure - Tursunov, Ikromjon Gulamovich; Okhunov, Abdurahim; Mamatkarimov, Odiljon Oxundadaevich (IIUM Press, International Islamic University Malaysia, 2018)
This paper discusses the strain sensitivity of silicon with deep levels under variable pressure. It is shown that in the pressure swing in silicon with deep levels, there is a redistribution of the primary spatial inhomogeneities in the distribution of impurities so that the electron-hole relaxation after stress relief will occur in the new potential relief.